The Impact of Using Indicative Concept Map Technique of Teaching on Students’ Reading Comprehension in the Region of Kurdistan A Co- Research Paper Submitted - Abbas, Nada Jabbar; Ghazal, Kusai Tawfiq (لارك, 2019)
Reading skill has not been given enough care by the teachers of English language in the classrooms so students are no more good readers. As a result students should be aware of the strategies that they can follow when they start reading in order to make the reading process a fruitful process. One of the reading techniques that help students comprehend what they read is the concept mapping technique of teaching (CM). The researchers conducted a study to investigate the effect of using the indicative concept mapping technique  on the students' reading comprehension achievement . Therefore, this study tries to answer the following question:“Is there a statistically significant difference between the mean scores attained by the experimental group and those attained by the control group on reading comprehension on the post-test that can be attributed to the concept mapping technique”?          To answer this question, the researchers selected two groups of students randomly to form the experimental and the control groups with (20) students for each group. The two groups set for pre-test to assure that the two groups are equivalent. The experimental group was taught reading comprehension (RC) lessons through the use of indicative concept map technique. On the other hand, the controlling group was taught by the traditional technique of teaching reading comprehension.           The findings revealed that there are significant differences between the mean scores attained by the experimental group and those attained by the control group in favor of the experimental group due to the use of Concept mapping technique; therefore, the researchers rejected the null hypothesis and accepted the alternative one which indicates that there is a significant differences between the experimental and the control groups. The researchers recommended in light of the findings that the students should be encouraged to follow the concept mapping technique while reading and to engage students in such activities that allow them to transfer more and more lessons into different types of concept maps.